(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2025)
The Venezuelan university is called upon to adopt a management approach that ensures its continuity amid significant transformations, in which communication must be an inherent instrument of power to achieve organizational goals. Given the importance of these factors, this study was conducted with the aim of determining the impact of communication on the management of institutional power in Venezuela’s leading universities. A qualitative approach was used, applying interviews with four key informants—executives from one public and one private university. Their responses revealed that universities operate under a classical, scientific, and bureaucratic administrative model, characterized by vertical communication. Therefore, a strategic management of communication is necessary to achieve relational power that fosters the construction of meaning through discourse aimed at guiding the actions of institutional members.